DECISION SUPPORT SYSTEM IMPLEMENTATION IN DETERMINING STUDENTS TO RECEIVE BOS FUNDING USING THE WASPAS METHOD - Napisah, Napisah; Muliono, Rizki; Khairina, Nurul; -, Muhathir (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
Success in learning and learning activities at SMA Asy-Syafiiyah Medan, is not only influenced by teachers, but also by student aspects such as attendance, parental income, activity participation, achievement scores, and discipline. To obtain optimal results, the authors designed an application using the Weighted Aggregated Sum Product Assessment (WASPAS) method that can determine students who receive BOS funds. After calculating 5 times with predetermined criteria, Rizki Ridho Silalahi's final result was 0.9197. The system designed for receiving BOS Fund assistance at SMA Asy-Syafiiyah Medan has been tested by inputting criteria data and carrying out the calculation process using the WASPAS method.